Neutrophil extracellular traps as therapeutics target in vascular aging - Mao, Jie; Wu, Shuang; Yan, Zelin; Huang, Guiping; Yu, Yihua (Frontiers in Immunology, 2025)
Blood vessels are critical in systemic aging with arteries stiffening and calcifying due to chronic inflammation and oxidative stress, driving age-related cardiovascular and cerebrovascular diseases. In this review, neutrophil extracellular traps (NETs) —web-like structures composed of decondensed chromatin, histones, and antimicrobial proteins released by neutrophils—are explored as therapeutic targets in vascular aging. NETs are vital for pathogen defense, but their excessive activation leads to inflammation and vascular pathologies, promoting endothelial dysfunction, inflammatory aging, and vascular remodeling in diseases such as hypertension, atherosclerosis, myocardial infarction, heart failure, atrial fibrillation, ischemic stroke, and Alzheimer’s disease. Increasing evidence supports that modulating NETs through inhibitors or scavengers can reduce inflammatory responses, preserve endothelial integrity, and improve prognosis. As a potential therapeutic target, growing attention has been directed toward exploring the balance between NET induction, inhibition, and degradation.